Do Criminal Background Checks in Hiring Punish? - Lee, Michael A. C. (2017)
Criminal background checks in the hiring process make it more difficult for former offenders to obtain employment at their market skill level. As a result, many former offenders end up underemployed or unemployed altogether. This obstacle to finding gainful employment is a harm, and this harm directly follows from a former offender’s criminal conviction. The harm can therefore be thought of as part of the punishment imposed on criminal offenders. However, unlike the formal punishment that a criminal offender receives through his sentence, the harm that follows the offender as he seeks employment after he has completed his formal sentence has no basis in punishment theory.1 Criminal background checks in hiring is a policy that aims at furthering employer interests, not punishing criminal offenders. For this reason, the punitive effect of criminal background checks often goes overlooked even though there are simple, straightforward ways to reform the process without abridging the purpose of protecting employers